PERANCANGAN SISTEM INFORMASI AKADEMIK BERBASIS WEB PADA MTSN 5 MUARO JAMBI - Ramadhan, Fauzan Purma; Dianda Rifaldi; Iriene Putri Mulyadi; Vanji Saputra (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2025)
The manual management of academic data has the potential to cause various obstacles, such as delays in grade distribution, data duplication, and input errors. This study aims to design a web-based academic information system at MTsN 5 Muaro Jambi as a solution to these problems. The system was developed using the Waterfall method with the PHP programming language and a MySQL database. The database design was carried out in a structured manner to support the integrity and efficiency of academic information management. The novelty of this study lies in the integration of grade management, attendance, and schedule features into a single web-based platform, which has never been implemented before at MTsN 5 Muaro Jambi. The system was designed to involve three main actors: the admin as data manager, teachers as data managers, and students as recipients of online academic information. The implementation results showed that the system was able to improve recording accuracy, accelerate information distribution, and support academic data transparency. Testing using the blackbox testing method proved that the system's main functions ran as needed, while user acceptance trials involving teachers, students, and administrative staff showed the system was easy to use and useful in supporting the academic process.